2020
DOI: 10.1126/scisignal.abe1202
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution structures of the SARS-CoV-2 2′- O -methyltransferase reveal strategies for structure-based inhibitor design

Abstract: There are currently no antiviral therapies specific for SARS-CoV-2, the virus responsible for the global pandemic disease COVID-19. To facilitate structure-based drug design, we conducted an x-ray crystallographic study of the SARS-CoV-2 nsp16-nsp10 2′-O-methyltransferase complex, which methylates Cap-0 viral mRNAs to improve viral protein translation and to avoid host immune detection. We determined the structures for nsp16-nsp10 heterodimers bound to the methyl donor S-adenosylmethionine (SAM), the reaction … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
184
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 168 publications
(189 citation statements)
references
References 64 publications
4
184
0
1
Order By: Relevance
“…This necessitates antiviral development 36 . The 2′-O-MTase nsp16 has been proposed as an appealing target for development of anti-coronaviral therapeutics 8, 11,28, 37 . Deletion of SARS-CoV nsp16 coding-region resulted in a blockade of viral RNA synthesis 18 , and nsp16 mutants have shown a strong attenuation in infected mice 19 .…”
Section: Discussionmentioning
confidence: 99%
“…This necessitates antiviral development 36 . The 2′-O-MTase nsp16 has been proposed as an appealing target for development of anti-coronaviral therapeutics 8, 11,28, 37 . Deletion of SARS-CoV nsp16 coding-region resulted in a blockade of viral RNA synthesis 18 , and nsp16 mutants have shown a strong attenuation in infected mice 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Protein expression, purification, and crystallization. Recombinant nsp16 and nsp10 proteins with 6xHis-tags removed were purified from Escherichia coli and crystallized as previously described (10).…”
Section: Methodsmentioning
confidence: 99%
“…2A). We previously showed that the cap binding site, also called the High Affinity Binding Site (HBS), is bordered by flexible loops that adopt an open conformation upon Cap-0 analog binding (10). Interactions of the nsp16 residues Tyr6828, Tyr6930, Lys6935, Thr6970, Ser6999 and Ser7000 with the Cap-0 analog and Cap-0-RNA are similar in both structures.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“… 17 Various structures of nsp10-nsp16 from SARS-CoV-2 in complex with SAM, SAH, RNA, and sinefungin have been recently deposited in the Protein Data Bank (PDB) that provide vast amounts of information on the interaction of substrates with nsp16 and could be used in structure-guided drug discovery. 27 , 28 …”
Section: Introductionmentioning
confidence: 99%